Highly Sensitive Bioluminescence Imaging Models for Chagas Disease Drug Discovery - John M. Kelly; Amanda F. Francisco; Shiromani Jayawardhana; Martin C. Taylor; Michael D. Lewis (Proceedings, 2017)
Chagas disease is caused by the insect-transmitted protozoan Trypanosoma cruzi, and is the most important parasitic infection in Latin America. [...]